Perception Matters: What Message Are We Sending to Faculty with Departmental Book Allocations?. Issue 4 (1st October 2016) - Powers, Bonnie
ABSTRACT: Perception can be everything. As librarians consider the ever-changing nature of the library's role on campus, they may want to adopt a philosophical approach to restructuring the traditional library materials budget from the perspective of perception rather than from the perspective of cost-cutting, creating staff efficiencies, or even collection development. By looking at the role faculty play in building the library's collection, conclusions can be formed about what the library's budget structure and budgetary interaction with faculty convey about the library's priorities as an institution and with regard to its role within the campus community as a whole.